RUANG REKREASI MUSIK DI PAPANGGO, TANJUNG PRIOK - Nicholas Antonio; Martin Halim (Jurusan Arsitektur dan Perencanaan, 2020)
It was found in the area of North Jakarta has a fairly high level of labor force participation. It can be concluded from this data that all levels of society in North Jakarta have jobs. With the changes from manual technology to high technology, It is through these circumstances that people must revolutionize technology that’s actually not ready to be faced by the community. This condition creates a lot of pressure on the community. According to North Jakarta BPS data, the labor force in Tanjung Priok reaches 66% and the rest are part of the non-workforce. So, the solution to reduce the level of saturation at work, namely providing a place for intermediary space, between the first and second places in the form of music and culinary recreation.